AquaNet - Zooplankton from Erken AquaNet platform, 2017-06-13–2017-09-11 - Erken Laboratory (Uppsala University, 2019)
Zooplankton information from grab samples taken from the AquaNet mesocosms. This data contains more specifically the number of individuals per taxonomic unit and biomass calculations.
Erken Laboratory (2019). AquaNet - Zooplankton from Erken AquaNet platform, 2017-06-13–2017-09-11 [Data set]. Swedish Infrastructure for Ecosystem Science (SITES). https://hdl.handle.net/11676.1/Yxleb8SQn4ulzthRMgBCceh4
Keywords: SITES AquaNet; Ecosystem functions; Food-web dynamics; Zooplankton; Soil Science; Markvetenskap; Agriculture, Forestry and Fisheries; Jordbruk, skogsbruk och fiske; Agricultural Science; Jordbruksvetenskap; Ecology; Ekologi; Multidisciplinary Geosciences; Multidisciplinär geovetenskap; Environmental Sciences; Miljövetenskap; Climate Science; Klimatvetenskap